2021
DOI: 10.1093/bjs/znab430.261
|View full text |Cite
|
Sign up to set email alerts
|

P-P39 Perioperative Interventions to Reduce Pancreatic Fistula following Pancreaticoduodenectomy: A Systematic Review and Meta-Analysis

Abstract: Background Many studies evaluate interventions to reduce POPF following PD, but often report conflicting results. Previous meta-analyses have generally included non-randomised trials and not considered novel interventions.  Aim To evaluate interventions to reduce postoperative pancreatic fistula (POPF) following pancreatoduodenectomy (PD) with level 1 data. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…A recent review demonstrated almost all of the randomized-controlled trials (RCTs) evaluating perioperative intervention strategies for POPF after PD to be underpowered. 3 Perhaps, risk stratification could allow for better evaluation of POPF mitigation strategies with future interventions directed to certain risk groups mostly benefiting from them. At any rate, studies examining the utility of the prediction models are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent review demonstrated almost all of the randomized-controlled trials (RCTs) evaluating perioperative intervention strategies for POPF after PD to be underpowered. 3 Perhaps, risk stratification could allow for better evaluation of POPF mitigation strategies with future interventions directed to certain risk groups mostly benefiting from them. At any rate, studies examining the utility of the prediction models are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…3,21 Some mitigation strategies explored have been different modalities of pancreatoenteric anastomosis in PD, stump closure mechanisms in DP, use of internal and external pancreatic stents, and perioperative somatostatin analogues. 3,22 Of these, pasireotide (a type of somatostatin analogue) has shown benefit in randomized controlled trials. 21,23 Individualized POPF risk estimation could provide clinicians and researchers a useful tool for controlling case-mix and assessing the effect of different mitigation strategies in a risk stratified setting.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although no specific anastomosis method has ultimately been shown to consistently reduce the rate of clinically significant pancreatic leakage 19 , there is some evidence to suggest that invagination methods are preferable when operating on high-risk patients with a soft pancreas and small pancreatic duct. 20 One international position statement and literature review by the International Study Group of Pancreatic Surgery (ISGPS) published in 2016 on pancreatic anastomoses concluded that after 2 decades of randomized controlled trials (RCTs) and metaanalyses the evidence was still inconclusive.…”
Section: Anastomosesmentioning
confidence: 99%